2008
DOI: 10.14723/tmrsj.33.825
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Membranes from Wood Materials and their Separation Properties

Abstract: Carbon membranes were prepared by coating thin layers of lignocresol derived from Hinoki cypress by the phase-separation method and then carbonizing the lignocresol by high frequency induction heating at a heating rate of 500°C/min. The thickness of the membrane formed on the outer surface of a porous alumina substrate was about 1000 nm. Carbon membrane with a high performance of gas permeation showed a high water-selectivity in pervaporation of water/alcohol separation. The separation factor increased with in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 5 publications
(5 reference statements)
0
8
0
Order By: Relevance
“…The thermogravimetric analysis of the lignocresol [7] showed that the weight of lignocresol decreased by approximately 45% in the range of 350-450ºC and then gradually decreased by 55% at 800ºC. The gaseous products evolved from the lignocresol included methylphenol, dimethylphenol and several compounds with higher molecular weight together with traces of carbon dioxide and methanol.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The thermogravimetric analysis of the lignocresol [7] showed that the weight of lignocresol decreased by approximately 45% in the range of 350-450ºC and then gradually decreased by 55% at 800ºC. The gaseous products evolved from the lignocresol included methylphenol, dimethylphenol and several compounds with higher molecular weight together with traces of carbon dioxide and methanol.…”
Section: Resultsmentioning
confidence: 99%
“…6 Gas permeation rates (R) at 35ºC and 1 atm through lignocresol membranes carbonized at 600ºC and 700ºC for 10 min in nitrogen atmosphere. 34 [3] 371-374 (2009) Transaction of the Materials Research Society of Japan Carbon membranes derived from lignocresol with a high performance of gas permeation also showed a high water-selectivity in pervaporation of water/alcohol separation [8].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…although it may open up a space for new research. In this sense, lignocresols, as polyphenolic extracts of lignocellulose and other liquefied wood products, represented an approach to synthesise CMSMs for gas separation [182][183][184][185][186][187]. Pyrolysis of these precursors was carried out over a temperature range of 400-800 °C and under vacuum or N 2 atmosphere.…”
Section: "Greener" Phenolic Carbon Membranes In Gas Separationmentioning
confidence: 99%
“…In the works of the research group of Kita et al and Koga et al[182][183][184][185], a lignocresol fraction was extracted from a lignin matrix by a phase-separation treatment with p-cresol and sulphuric acid. This phenolic fraction was mixed with methyl ethyl ketone and used to coat the outer face of an alumina tube.…”
mentioning
confidence: 99%